2021
DOI: 10.3390/v13081458
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Clinical Outcomes of 116,539 Patients Hospitalized with COVID-19—Poland, March–December 2020

Abstract: The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) causes Coronavirus Disease 2019 (COVID-19). This study aimed to characterize patients hospitalized with COVID-19 in Poland between March and December 2020, as well as to identify factors associated with COVID 19–related risk of in-hospital death. This retrospective analysis was based on data from the hospital discharge reports on COVID-19 patients hospitalized in Poland between March and December 2020. A total of 116,539 discharge reports on pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
3
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 23 publications
2
20
3
1
Order By: Relevance
“…Previous studies showed that older age, male sex, and presence of comorbidities are associated with severe course of COVID 19 [1,3,[22][23][24]. However, there is limited data primarily focused on the factors associated with the development of ARDS among patients hospitalized with COVID-19, as well as the risk of in-hospital death among patients with COVID-19-associated ARDS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that older age, male sex, and presence of comorbidities are associated with severe course of COVID 19 [1,3,[22][23][24]. However, there is limited data primarily focused on the factors associated with the development of ARDS among patients hospitalized with COVID-19, as well as the risk of in-hospital death among patients with COVID-19-associated ARDS.…”
Section: Discussionmentioning
confidence: 99%
“…All patients with a medical diagnosis of COVID-19 (diagnosis codes: U07.1 or U7.02) were included in the analysis. A similar approach was applied in previous papers on hospitalized patients with COVID-19 in Poland, where the data source was medical registers [22][23][24].…”
Section: Covid-19 Reportingmentioning
confidence: 99%
“…Many studies have shown that older age and comorbidities, such as cancer, are risk factors for severe disease, complications, and death from COVID-19 [16,17]. For example, Gujski et al [5] showed that older age, male gender. and the presence of comorbidities is associated with the risk of in-hospital death associated with COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…Each patient with COVID-19 requiring hospitalization had the option of free hospitalization under the public health care system. Due to differences in health care systems and the number of tests for SARS-CoV-2 infections in individual countries, data on the trend of COVID-19 infections due to socio-demographic features and the presence of diseases such as cancer are necessary [5].…”
Section: Introductionmentioning
confidence: 99%
“…Uważa się, że pochodzi on od zwierząt takich jak nietoperze, węże czy łuskowce, a do transmisji na człowieka doszło na targu rybnym [1,3]. Do zakażenia dochodzi głównie drogą kropelkową, gdy osoba zakażona SARS-CoV-2 kicha, kaszle lub mówi [5,6]. Objawy choroby COVID-19 obejmują gorączkę, kaszel i zmęczenie, rzadziej występują nudności i biegunka [5,7].…”
Section: Wprowadzenieunclassified